The mapping and conservation status of architectural remnants from the time of the Sorocabana railway at Avaré Ecological Station and in the rural neighborhood of Andrade e Silva - Primos, Mariana Patty Guilger; Enokibara, Marta (Revista Nacional de Gerenciamento de Cidades, 2020)
The Andrade e Silva station and Forest Garden were installed, respectively, in 1895 and 1939 in the municipality of Avaré, as support for the operation of the “Estrada de Ferro Sorocabana” [Sorocabana railway]. With the change in the layout of the tracks, the surroundings of the station, which was configured as a prosperous urban center, became a rural neighborhood, and the Forest Garden an Ecological Station. In this context, the article aims at the mapping and conservation status of the architectural remnants still present in these locations. The specific objective is to provide subsidies for public policy decision making: Review of the “Plano de Manejo da Estação Ecológica de Avaré” [Avaré Ecological Station Management Plan] (EEA), belonging to the “Instituto Florestal” [Florestal Intitute] (IF) of the São Paulo State government, and the “Plano Diretor Municipal de Avaré” [Master Plan of the Municipality of Avaré]. Methodologically, it focused on primary documentation (Railway Reports, IF Reports, notary’s certificates and legislation), cartographic, iconographic documentation, interviews and on-site visits to map the area in relation to its original composition (period of the railway) and the current situation. The survey enabled the mapping of the architectural remnants present in the neighborhood, in the EEA, as well as the original route that had been taken by the railway. The iconographic rescue allowed to pinpoint the location of buildings that no longer exist. The survey made it possible to ascertain that some architectural remnants present in the EEA have been restored (chapel), others need restoration (in the neighborhood and elements along the old railway track bed), but all need to be integrated into a joint policy between city and state, as they are important part of the history, memory and culture of the municipality of Avaré.